IMPLEMENTASI 9 PILAR PENDIDIKAN TERHADAP PENANAMAN NILAI KARAKTER PADA ANAK USIA DINI DI RA AL-IZZAH KOTA SERANG: IMPLEMENTATION OF THE 9 PILLARS OF EDUCATION IN INSTILLING CHARACTER VALUES IN EARLY CHILDHOOD AT RA AL-IZZAH SERANG CITY - Salam, Lania Rizka; Ramlaini, Intan; Nuroh, Siti; Farah, Dhiya; Pramesti, Adinda Ardhita; Maulinda, Tasya; Rosidah, Laily (Universitas Islam Malang, 2024)
Character value cultivation in children should begin at an early age through early childhood education institutions, via learning activities tailored to the needs of young children. One method is the implementation of the 9 Pillars of Education in instilling character values in early childhood at RA Al-Izzah, Serang City. The purpose of this study is to determine the implementation of the 9 Pillars of Education in instilling character values in early childhood at RA Al-Izzah, Serang City. The method used is qualitative with a case study approach. Data collection was carried out through data triangulation, and data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation begins with the preparation of RPPH and the application of character cultivation activities during the first 10 minutes of learning. Supporting factors include adequate facilities, competent teachers, exemplary behavior, habituation, and family harmony. Inhibiting factors in instilling character values in early childhood include limited time, differing child temperaments, lack of cooperation between parents and teachers, and social environmental factors. The conclusion is that the implementation of this learning is very important as the 9 Pillars of Character can enhance the development of children into better individuals in various aspects of life.